Comparative rheological features of radiated Darcy-Forchheimer flow of micropolar and second grade fluid with cross diffusion and Arrhenius activation energy - S. Bilal; Muhammad Yasir; Ali Hasan Ali (Partial Differential Equations in Applied Mathematics)
The main intension of this study is to scrutinize the transient flow characteristics of two different non-Newtonian models of micropolar fluid and second grade fluid subject to a stretchable Riga plate. This novel study communicates with the rotational motion of microelements by taking into account the strong and weak concentrations and incompressible Darcy Forchheimer flow features of second grade fluid. In the context of Dufour and Soret effects, the cross-diffusion process is analyzed in the mechanisms of mass and heat transport. Moreover, Buongiorno model is taken into account to deliberate the random movement of particles and thermophoretic effects in both considered fluids. The consequences of convective constraint, Arrhenius activation energy, and joule heating are also incorporated. The framework of ordinary dimensionless equations is accomplished by deploying convenient variables and numerically processed via reliable bpv4c technique in MATLAB. The rheology of both considered fluids is compared through graphics regarding different concentration level and pertinent parameters. Micropolar fluid has higher intensity of its dynamical behavior as compared to second grade fluid. Moreover, the improved activation energy parameter lowers the nature of both considered fluids.